Predictors of postpandemic preparedness for special pathogens - Morgan M. Kuhnly; Caitlin M. Adams Barker; Kathleen O. Stewart; Justin J. Kim (Cambridge University Press, 2024)
In this survey of 31 hospitals, large metropolitan facilities had a 9.5-fold odds of reporting preparedness for special pathogens; hospitals with special pathogens teams had a 14.3-fold odds of reporting preparedness for special pathogens. In the postpandemic world, healthcare institutions must invest in special pathogen responses to maximize patient safety.